A narrow range multielectrochromism from 2, 5-di-(2-thienyl)-1H-pyrrole polymer bearing pendant perylenediimide moiety. (February 2015) - Sefer, Emre; Bilgili, Hakan; Gultekin, Burak; Tonga, Murat; Koyuncu, Sermet
Abstract: A new 2, 5-di-(2-thienyl)-1H-pyrrole (SNS) moiety containing perylenediimide (PDI) acceptor as pendant side chain has been synthesized for an electroactive monomer and then directly deposited onto ITO/glass surface via electrochemical polymerization process. The observed electronic interaction only at the excited state due to the presence of phenylene spacer between SNS-donor and PDI-acceptor moiety leads to efficient fluorescence quenching. This charge separation behavior was also proved by theoretical DFT calculations. Thin films of the polymer electropolymerized onto transparent electrode exhibited ambipolar multi-electrochromic behavior including purple, violet-red-khaki-blue colors in both anodic and cathodic regime only between −1.2 and 1.0 V. We further demonstrated that this polymer film has a high contrast ratio (Δ T = 45% at 900 nm), a faster response (0.5 s), high coloration efficiency (254 cm 2 C −1 ) and retained its performance by 92% even after 5000 cycles. Graphical abstract: Highlights: 2, 5-di-(2-thienyl)-1H-pyrrole (SNS) based polymer containing perylenediimide (PDI) was synthesized. The polymer exhibited generation of an attractive palette of colors in a narrow range of −1.2–1.0 V. Remarkable fluorescence quenching in the PDI core was observed due to efficient intramolecular electron transfer at the excited state.